A Novel Intergenic Gene Between SLC8A1 and PKDCC-ALK Fusion Responds to ALK TKI WX-0593 in Lung Adenocarcinoma: A Case Report - Du, Jia; Wang, Baoming; Li, Mengxia; Wang, Chunyang; Ma, Tonghui; Shan, Jinlu (Frontiers in Oncology, 2022)
Background: Expanding the druggable novel ALK fusions list is crucial to the precise treatment of cancer patients with positive ALK fusions. The intergenic-ALK fusions accounted a substantial proportion of ALK fusions. However, they were often considered no clinical significance due to the obscure functional partner in the fusions. In this case report, a patient carrying intergenic-ALK fusion present excellent outcome after taking the new second generation tyrosine kinase inhibitor candidate, WX-0593. Case presentation: A 47-year-old Chinese female patient diagnosed as IVB lung adenocarcinoma was admitted to the hospital with big lesions in the left lobe of lung. After one week of front-line adjuvant chemotherapy, no response was found. In the search for potential therapeutic targets, a novel ALK rearrangement generated by a fusion of the SLC8A1/PKDCC intergenic region to the intron 19 of ALK was presented after next generation sequencing. High expression of ALK was confirmed by immunohistochemistry. Patient was referred to enroll in a phase III clinical trial (NCT04632758) and received an orally active second generation ALK inhibitor WX-0593. Partial response was obtained more than 17 months, and without significant side effects. Conclusion:In summary, a non small cell lung cancer patient with novel intergenic-ALK fusion, whose breakpoint was located between SLC8A1 and PKDCC, benefited from a potent ALK tyrosine kinase inhibitor candidate WX-0593. This finding extended the scope of targetable ALK fusions and underscored the advantage of next generation sequencing in mining rare but functional ALK fusions, which eventually bring benefits to the patients.